Haitian orphan population and protective factors against caries - Madelyn Rea (University Library System, University of Pittsburgh, 2016)
Objective In Haiti, families were torn apart and children were left orphans after the 2010 earthquake. In the aftermath of this natural disaster many children were relocated to orphanages across the country and adopted internationally. Years later these children find themselves catching up in growth physically, mentally and emotionally after an extremely traumatic event during a crucial time in their health development. Another important marker of development is the primary dentition and the presence of caries.  We report estimates of early childhood caries (ECC) frequency, risk factors and quality of health among Haitian children. Methods Medical and dental professionals conducted a descriptive cross sectional study through the Pittsburgh Kids Foundation and their partnership with IDADEE children's home, EBAC orphanage and New Vision Children's home. Vital signs were taken and recorded to create a health/growth history for each child. Brief dental screenings were conducted and topical fluoride treatments were administered. Risk factors and quality of health information was obtained from discussions with the caregivers present. The children and caregivers were given oral hygiene education and supplies (i.e. toothbrushes, toothpaste, floss).  Results Physical exams and dental screenings were conducted on the 40 children ages 3-10 years of age living in the IDADEE children's home. Two children had cavitated teeth. Eight children had teeth that were stained. Four children had evidence of dental trauma. 26 out of the 40 children had otherwise healthy dentition. Conclusion The IDADEE children's home and New Vision Children's home have hopes to expand their capacity with new construction scheduled to be finished in 2016. As more children enter these homes action is needed to educate caregivers on ways to identify high-risk children to prevent ECC and ways they can be treated before irreversible damage is done to the developing permanent dentition.